Function, Evolution, and Composition of the RpoS Regulon in Escherichia coli - Schellhorn, Herb E. (Frontiers in Microbiology, 2020)
For many bacteria, successful growth and survival depends on efficient adaptation to rapidly changing conditions. In Escherichia coli, the RpoS alternative sigma factor plays a central role in the adaptation to many suboptimal growth conditions by controlling the expression of many genes that protect the cell from stress and help the cell scavenge nutrients. Neither RpoS or the genes it controls are essential for growth and, as a result, the composition of the regulon and the nature of RpoS control in E. coli strains can be variable. RpoS controls many genetic systems, including those affecting pathogenesis, phenotypic traits including metabolic pathways and biofilm formation, and the expression of genes needed to survive nutrient deprivation. In this review, I review the origin of RpoS and assess recent transcriptomic and proteomic studies to identify features of the RpoS regulon in specific clades of E. coli to identify core functions of the regulon and to identify more specialized potential roles for the regulon in E. coli subgroups.